Do (Perceptions of) Electoral Polling Affect Voters' Behavior? Campaigns, Partisan Bias, and Strategic Voting - Castro Cornejo, Rodrigo (Revista Latinoamericana de Opinión Pública, 2023)
The manuscript highlights the major role that partisanship plays in moderating voters’ interpretation of polling information and incentives to behave strategically. While prior studies highlight that partisans are less likely to vote strategically as the expressive costs of defection increase, this study sheds light on the conditions in which voters—even partisans—behave strategically and which contribute to an increase in the proportion of voters who change their vote intention during campaigns. Only partisans informed about polls are able to overcome their partisan bias and engage in strategic voting. By taking strategic voting into account in the study of campaigns, the present work builds a bridge between the campaigns effects literature and studies on strategic voting.